The Mediating Role of Consumer Trust in the Influence of Marketing Mix on Consumer Decisions to Stay at Bebek Cottage Sanur - Putu Ayu Nadya Pradnyagita (International Journal of Management Science and Information Technology, 2024)
This study aims to analyze the role of consumer trust as a mediating variable in the relationship between marketing mix and consumer decisions to stay at Bebek Cottage Sanur, Bali. The background of this study is based on the significant impact of the COVID-19 pandemic on the hospitality industry, especially in Bali, which forced many hospitality businesses to close their operations. As a newcomer established amidst this instability, Bebek Cottage Sanur implemented a marketing mix strategy consisting of product, price, place, promotion, people, process, and physical evidence to attract consumers. A quantitative approach was used in this study, using path analysis techniques to test the direct and indirect effects of the marketing mix on consumer decisions through consumer trust. Data were obtained through questionnaires distributed to 136 respondents who stayed at Bebek Cottage Sanur during the high season. The results showed that marketing mix positively and significantly affects consumer decisions, both directly and indirectly, through consumer trust. Consumer trust is proven to be a significant mediator, where increasing consumer trust in Bebek Cottage Sanur can strengthen the effect of the marketing mix on consumer decisions to stay. This study makes an essential contribution to the marketing literature by confirming that consumer trust is a critical element in maximizing the effectiveness of the marketing mix. The practical implications of these findings emphasize the importance of hotel management focusing on developing marketing mix strategies and managing and strengthening consumer trust to achieve long-term loyalty and future business success.